Purified PTEN-Long Induces Liver Cancer Cells to Undergo Autophagy and Apoptosis - Tan, Lin; Xu, Zeping; Mao, Qiqi; Zhou, Shaocheng; Zhu, Jie; Zhang, Xie; Li, Hong (Frontiers in Surgery, 2022)
Background PTEN-Long is a translational variant of phosphatase and tensin homolog deleted on chromosome 10 (PTEN). This tumor suppressor is frequently lost or mutated and even it has been shown as the determinant in several human tumors. Therefore, we will determine the significant roles of PTEN-Long in the development of liver cancer. Methods In the present study, we characterized the antitumor effects of PTEN-Long and PTEN in proliferation, migration of HepG2 cells, apoptosis and autophagy in liver cancer cells. To extends, we have also measured the effects of purified PTEN and PTEN-Long in the above index of HepG2 cells. Results PTEN and PTEN-Long were ectopic-expressed in HepG2 cells, and their phenotypic effects were recorded. As expected, there was less expression of PTEN-Long and PTEN in liver cancer samples than in paired normal tissues. Ectopic expression of PTEN-Long or PTEN significantly decreased the proliferation and migration of HepG2 cells and increased apoptosis. PTEN ectopic-expression increased the number of GFP-/RFP+-LC3 puncta and levels of beclin-1 and LC3BII/LC3BI, suggesting autophagy induction. Purified PTEN-Long freely entered cells, decreased proliferation, and increased autophagy and apoptosis, while purified PTEN did not. Conclusions Our results identify an antitumor function of purified PTEN-Long and suggest its potential utility for liver cancer treatment.